School for young children : developmentally appropriate practices - Wolfgang, Charles H.; Wolfgang, Mary E. (Boston : Allyn and Bacon, 1999)
Models of teaching young children. Understanding the young child's play. Organizing classroom space and play materials. Play-activity learning: goals and teaching methods. New learning through thematic-project experiences...
Keywords: Education; Early childhood education; Early childhood education -- United States -- Handbooks, manuals, etc